Toward operational methods for the assessment of intrinsic groundwater vulnerability: A review. Issue 9 (2nd May 2016) - Wachniew, Przemysław; Zurek, Anna J.; Stumpp, Christine; Gemitzi, Alexandra; Gargini, Alessandro; Filippini, Maria; Rozanski, Kazimierz; Meeks, Jessica; Kværner, Jens; Witczak, Stanislaw
ABSTRACT: Assessing the vulnerability of groundwater to adverse effects of human impacts is one of the most important problems in applied hydrogeology. At the same time, many of the widespread vulnerability assessment methods do not provide physically meaningful and operational indicators of vulnerability. Therefore, this review summarizes (i) different methods used for intrinsic vulnerability assessment and (ii) methods for different groundwater systems. It particularly focuses on (iii) timescale methods of water flow as an appropriate tool and (iv) provides a discussion on the challenges in applying these methods. The use of such physically meaningful indices based on timescales is indispensable for groundwater resources management.